(Biblical) creation of value. (13th August 2010) - Fernandes, Antonio S.C.
This paper proposes a definition and an algorithm to compute the value created in an economic process. The created value is the amount of value, from the gross value added, that exceeds a minimum value to return and the latter is defined as the quantity of value that should be returned to the economic unit's stock of value in order to keep constant its capacity to reproduce the same value. Also, the concept of value is explored through a brief epistemological analysis, concluding that it reflects human knowledge. It is argued that the increase of human knowledge and of its products is mirrored by the creation of value. The creation value algorithm is applied to the Portuguese economy, the results of which are compared with results for other European countries and Japan.